The Impact of the Gig Economy on Product Quality Through the Labor Market: Evidence from Ridesharing and Restaurant Quality - Shin, Minkyu; Shin, Jiwoong; Ghili, Soheil; Kim, Jaehwan (Management Science, 2023)
This paper seeks to demonstrate the impact of the gig economy on product quality in seemingly unrelated local industries through the labor market. Our empirical context is the quality of service for restaurants in the city of Austin, and we examine how they were impacted by the exogenous exit and reentry of rideshare platforms, Uber and Lyft, because of regulatory changes. We leverage these exogenous shocks and combine them with sentiment-analyzed data from Yelp reviews that capture how customers assess the quality of service at each restaurant. We show that, compared with control cities, customers in Austin become more negative about service quality when Uber and Lyft are present in the city. Additionally, we use rich data on employee turnover and wages to demonstrate that service staff turnover increases in Austin when Uber and Lyft are present compared with the control cities. We also conduct several additional studies and robustness checks that are all congruent with our hypothesis that Uber and Lyft lower the quality of service in Austin restaurants by raising their staff turnover. Together, these results suggest significant ramifications of the gig economy on the broader industries through the labor market. This paper was This paper was accepted by Matt Shum, marketing. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2022.4481 .